2009
DOI: 10.1159/000253757
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Suppress Growth in Neonatal Cardiomyocytes Co-Expressing AT<sub>2</sub> and AT<sub>1</sub> Angiotensin Receptors

Abstract: Background: Perinatal glucocorticoid treatment is associated with hypertrophic cardiomyopathy, but the cellular mechanism is controversial. An underlying interaction between glucocorticoids and the renin-angiotensin system may be important, but whether glucocorticoids modulate angiotensin II (AngII)-dependent cardiomyocyte growth responses in the neonate has not been investigated. Objectives: The major aim of this investigation was to determine whether glucocorticoids modulate the neonatal cardiomyocyte growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Involvement of the Akt signaling pathway in the heart tissue indicates the involvement of non-genomic actions of Dex in the development of side effects in the heart characterized by its reduced size compared to the controls. This can be related to the repressive effect of Dex on the proteins involved in the cell cycle [40] leading to suppression of the growth of cardiomyocytes [41] and a decrease in heart weight due to the inhibition of myocyte mitotic activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the Akt signaling pathway in the heart tissue indicates the involvement of non-genomic actions of Dex in the development of side effects in the heart characterized by its reduced size compared to the controls. This can be related to the repressive effect of Dex on the proteins involved in the cell cycle [40] leading to suppression of the growth of cardiomyocytes [41] and a decrease in heart weight due to the inhibition of myocyte mitotic activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…In neonates, complicated and sometimes contradictory accounts have also been noted. Studies have revealed that the glucocorticoid treatment is associated with hyperplasic [ 30 ], hypertrophic [ 31 , 32 ] or no effect on the growth [ 33 ] of cardiomyocytes, as analyzed by the protein to DNA ratio. Formation of binucleated myocardial cells is regarded as an early indicator of transition of hyperplasia to hypertrophic growth [ 10 ], indicating ceasing of proliferation of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Its primary effector hormone, angiotensin II (Ang II), not only mediates immediate physiological effects of vasoconstriction and blood pressure regulation but is also implicated in inflammation, endothelial dysfunction, atherosclerosis, hypertension and cardiac hypertrophy in a series of CVDs . Many studies support the observation that Ang II has direct effects on myocardial cells, including cardiomyocyte growth, accumulation of extracellular matrix and hypertrophy . These effects are known to be mediated by angiotensin type 1 receptor (AT1R), demonstrated by the fact that AT1R antagonists prevent Ang II‐induced cardiac hypertrophy in rats .…”
Section: Introductionmentioning
confidence: 99%